Kurt Johannesson: The Renaissance of the Goths in Sixteenth-Century Sweden. Johannes and Olaus Magnus as Politicians and Historians. Translated and edited by James Larson. (University of California Press, 1991). 282 s. - Jespersen, Leon (Historie/Jyske Samlinger, 1993)
-